Effects of online commenter sex cues and news receiver sex on commenter credibility. (December 2021) - Bhandari, Manu; Emery, Matthew; Scott, Sarah; Wolfgang, David
Online comments can affect news receivers' news perceptions. But the role of individual online comment sources is still poorly understood. Using Sundar's TIME (Theory of Interactive Media Effects) theory, this experiment examined the effects of commenter sex cues and news receiver sex on commenter credibility. Commenters with female (vs. male) names were rated higher in source credibility, and female news receivers were generally more likely to rate commenters higher on source credibility. Theoretical and practical implications are discussed.